(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Preterm labor is an obstetric emergency. Magnesium Sulfate (MgSO4) is often used as a first-line therapy for that purpose as it is a highly effective tocolytic with fewer side effects than other tocolytics. This study aimed to evaluate effectiveness of MgSO4 as a tocolytic agent in preterm labor. Materials and methods: A prospective comparative study was conducted in the Department of Obstetrics and Gynecology of CMCH, Chattogram, from June 2020 to November 2020. One hundred singleton pregnant women with preterm labor were included in this prospective comparative study. Patients were divided into two groups according to their cervical dilatation. Fifty patients who as tocolytic (Group A) and for 50 patients who had cervical dilatation >4 cm, spontaneous vaginal delivery was allowed (Group B). Both groups were observed for at least 48 hours to see labor progression. had cervical dilatation <4 cm got an injection of MgSO4 Results: Both groups were comparable regarding their demographic and obstetric characteristics. In Group A, 23 (46%) patients needed 30 minutes- 1 hour for the arrest of preterm labor compared to only 1 (2%) patient’s preterm labor was arrested <30 minutes in Group B (p<0.001). In Group A, most of the patients (76%) had 24-48 hours of delay in their preterm labor compared to 98% of patients who had experienced no delay in their preterm labor in Group B (p<0.001). Regarding side effect, most of the 37(74%) patients had hot flashes, followed by vomiting in 23(46%) nausea in 21(42%) headache in 13(26%) and hypotension in 7(14%) patients. Conclusion: The present study revealed that MgSO4 is an effective tocolytic agent with some tolerable and manageable side effects. JCMCTA 2025 ; 36 (1) : 124-128